Peculiarities of Studying Family Law in Islam - Yusupova Nigora (Zien Journals, 2022)
Today, it is important to examine the historical, legal, cultural and moral aspects of family relations in Islamic law, as well as their settlement with general social, socio-historical, socio-economic, legal, educational and organizational bases. This article examines the universal values and ideas of philanthropy, especially the oriental moral education set out in the views of the scientists of Maverannahr relating to family relationships. Also, the article emphasizes and analyzes the importance and role of family rules in Islam, its peculiar properties, socioeconomic, cultural and educational bases that are very effective in educating members of the family in the spirit of a national idea, values and patriotism.
Keywords: family problems; matrimonial relationships; women rights; family code law